PENGARUH DISIPLIN KERJA, MOTIVASI DAN KESEJAHTERAAN TERHADAP KINERJA PEGAWAI DI KSOP KELAS I PANJANG - Suryanto, Suryanto; Rika Lestari, Winda (Jurnal Bisnis Darmajaya, 2026)
This study aims to analyze the role of Work Discipline, Motivation, and Welfare on the Performance of KSOP Class I Panjang employees. The research problem is the decline or inconsistency in performance in several strategic areas that require further attention and improvement. This study uses a quantitative approach with a survey method, where data is collected through questionnaires from 101 respondents selected through saturated sampling. Data analysis techniques are conducted using multiple linear regression with the assistance of SPSS version 26.0 statistical software. The results of the study indicate that partially, Work Discipline has a positive and significant effect on employee performance, followed by motivation having a positive and significant effect on employee performance. Likewise, Welfare has a negative and significant effect on employee performance. The results of simultaneous testing showed that work discipline, motivation, and welfare have a positive significant effect on the Performance of Employees at KSOP Class I Panjang. These findings indicate that the results of this study reinforce the view that improving the performance of employees at KSOP Class I Panjang requires a balanced human resource management strategy, including the enforcement of work discipline, enhancement of employee motivation, and provision of adequate welfare as supporting factors for sustainable performance .Keywords: Work Discipline, Motivation, Welfare, Employee Performance, KSOP Kelas I Panjang